Enhancing Employability: The Crucial Role of Soft Skills in Tackling Unemployment - Kawitkar, Suresh S. (International Journal for Multidisciplinary Research (IJFMR), 2023)
Soft skills play a pivotal role in employee success in the private service sector. This research explores the significance of soft skills and their impact on individual and organizational performance within the sector. A mixed-method research approach involving surveys and interviews with a substantial sample of employees from diverse private service organizations was employed. The study highlights the critical relationship between soft skills and employee success, emphasizing the challenges and opportunities in enhancing these skills.
ISME
Keywords: Soft skills; Private service sector; Employee success; Skill development; Organizational performance